Client's assessment of the quality of care of family planning services in the rural health unit of Pavia, Iloilo. - Basas, Orchid Joy B.
Family Planning Studies in the Philippines had grown into enormous number. They are mostly centered on the acceptance of the various contraceptive methods by the couple and do not usually focus on the quality of care of family planning services. This study was conducted primarily in order to determine the clients' assessment of the three aspects of Quality of Care of Family Planning Services (choice of methods, information given to clients and mechanisms for continuity of use) provided by the Rural Health Unit in Pavia., The respondents were thirty-five (35) married women of reproductive age (15-49). The data were analyzed using simple frequency counts and percentages. The result of the study revealed that IUD and pills are the most offered contraceptive methods in the clinic. Other methods that are being offered include condoms, injectables, rythm, withdrawal, ligation and vasectomy. Most of the respondents preferred IUD and pills as their method. It also revealed that the respondents were informed about the side effects and effectiveness of their chosen method. Most of them also were able to discuss what they know about their chosen method. With regards to information service, most of the respondents were informed by the health worker regarding their chosen method. The study also revealed that the mechanism used by the health worker to ensure continuity of sue is through verbal means and by pressuring the respondents to go back to the clinic. By average, the clients' assessment of the quality of care of family planning services is very good which means that they are satisfied with the services they get from the clinic.